On the Widths of Bands in the Infrared Spectra of Oxyanions. Issue 6 (June 2018) - Griffiths, Peter R.; Eastman Fries, Brandy; Weakley, Andrew T.
It is well known that the antisymmetric stretching (ν3 ) band in the mid-infrared spectra of oxyanion salts is usually very broad, whereas all the other fundamental bands are narrow. In this paper, we propose that the underlying cause of the increased width is the effect of the very high absorption index of this band for samples prepared with a range of particle sizes. When oxyanion salts are ground, the diameter of the resulting particles usually varies from less than 100 nm to about 2 µm. While the peak absorbance of the ν3 band of the smaller particles (diameter < 200 nm) is less than 1, that of the larger particles can be as high as 6. We show that the average transmittance of these particles leads to a significant band broadening, especially when there are small voids in the resulting sample. Although the effect is always seen in the spectra of alkali halide disks and mineral oil mulls, it is also seen in diffuse reflection and attenuated total reflection (ATR) spectra. Because the depth of penetration of infrared radiation below 1500 cm −1 is less than 1 µm for ATR spectra measured with a germanium internal reflection element (IRE), the width of the ν3 band is lower than that of ATR spectra measured with an IRE of lower refractive index such as diamond on zinc selenide.